Role of intraseasonal and interannual processes in ocean heat content anomalies east of Mindanao - Zhen Li; Linlin Zhang; Mengmeng Li; Weiqi Song; Xiaoluan Yan; Tangdong Qu (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Ginsenoside Rk1 reprograms ‘cold’ cancer cell membranes into a ‘hot’ antigen repertoire for highly immunogenic cancer vaccines - Fangming Dong; Linlin Qu; Lebin Wang; Jing Zhao; Zhiguang Duan; Xueqing Yu; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Probiotics as a biocontrol strategy against Salmonella in poultry: A global meta-analysis - Mingjuan Qu; Lisheng Zhang; Jianlong Zhang; Xin Yu; Linlin Jiang; Hongwei Zhu; Xingxiao Zhang (Food Control, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Carbonized polymer dots as drivers of modernization in Chinese Herbal Medicine - Linlin Zhang; Ying Cheng; Xin Yang; Xiaoyu Chang; Siyu Lu; Bai Yang; Xiaoli Qu (Science Bulletin, 2026)

Harnessing β-glucans for immune regulation: Bridging structural diversity, therapeutic potential, and functional food development - Xue Wang; Linlin Ma; Chen Chen; Lina Ma; Xian Qu; Ai Ren; Yifa Zhou; Hairong Cheng (Carbohydrate Polymers, 2026)

Inhibitory effects of nisin and ε-polylysine on the microbial cell structure and physiological function of Bacillus amyloliquefaciens and applications in bread preservation - Min Qu; Xin Zhang; Xiuqing Zhu; Jingbo Kang; Linlin Liu; Mingshou Lv; Ying Zhu; Bingyu Sun (Food Bioscience, 2025)

Engineering yeast expression platforms: Advanced strategies for heterologous protein production and glycosylation modification - Hao Li; Taichi Chen; Zikun Zhang; Qiyi Jiang; Weigang Yuwen; Linlin Qu; Rongzhan Fu; Chenhui Zhu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Ginsenoside, a potential natural product against liver diseases: a comprehensive review from molecular mechanisms to application - Shiyan Shang; Haixia Yang; Linlin Qu; Daidi Fan; Jianjun Deng (Critical Reviews in Food Science and Nutrition, 2025)

Effects of ultrasound on the structure and properties of soy protein gels prepared with different 11S/7S ratios - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Hydrocolloids, 2025)

Dynamic reversible thermochromic camouflage smart textiles for temperature visualized personal healthcare and thermal management - Weiyi Zhang; Shuo Luan; Yuyan Fang; Linlin Zhu; Yang Yang; Mingwei Tian; Lijun Qu; Tingting Fan; Jinlei Miao (Chemical Engineering Journal, 2025)

Predictive modeling and mechanistic interpretation of single electron transfer reactivity between antibiotics and reactive halogen species - Linlin Dong; Chenxuan Zong; Jiao Qu; Fangyuan Cheng; Ya-nan Zhang (Journal of Hazardous Materials, 2025)

Hematopoietic responses to metal-organic frameworks in adult mice following pulmonary exposure - Min Li; Linlin Yao; Yuanyuan Wang; Jie Gao; Junjie Ma; Yaquan Liu; Yun Ding; Xuehan Zheng; Liqun Chen; Runzeng Liu; Li Zeng; Guangbo Qu; et al. (Journal of Environmental Sciences, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Ginsenoside Rk1 Ameliorates Non-Alcoholic Fatty Liver Disease by Targeting CD36 to Modulate the AMPK Signaling Pathway - Yuqing Wu; Zhiguang Duan; Linlin Qu; Yannan Liu; Xiaoxuan Ma; Daidi Fan (Food Research International, 2025)

Differences in the distribution of exogenous nucleotide intake in the colon of neonatal rats and its impact on early-life metabolism, gut, gut microbiota, and skeletal development - Zhihao Qu; LiLi Zhu; Min Guo; Kexin Shang; Peijun Tian; Linlin Wang; Gang Wang; Heng Zhang; Wei Chen (Food Bioscience, 2025)

Tendon injury repair strategy driven by supramolecular hydrogen bonding and dynamic covalent bond self-assembly microspheres - Taishan Liu; Xiaoxuan Ma; Chenhui Zhu; Yu Mi; Jing Zhao; Linlin Qu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

The role of immunoglobins in atherosclerosis development; friends or foe? - Linlin Zhang; Peize Li; Yuhui Li; Wantong Qu; Yanyu Shi; Tianyang Zhang; Ying Chen (Molecular and Cellular Biochemistry, 2025)

Understanding the effect and mechanism of ε-polylysine on the improvement of tofu storage quality via biofilm inhibition by Bacillus licheniformis and Bacillus amyloliquefaciens - Jingbo Kang; Xin Zhang; Yuyang Huang; Ying Zhu; Linlin Liu; Bingyu Sun; Min Qu; Xiuqing Zhu (Food Bioscience, 2025)

Exosomal miR-27a-5p attenuates inflammation through Toll-like receptor 7 in foodborne Salmonella infections - Mingjuan Qu; Shengfa Su; Linlin Jiang; Xin Yu; Jianlong Zhang; Hongwei Zhu; Kexue Han; Xingxiao Zhang (Veterinary Microbiology, 2025)

Effect of freezing-thawing treatment on the quality and structure of soymilk gels induced by different coagulants - Ying Zhu; Wenhua Lei; Lidan Qiu; Simiao Liu; Ruqi Guo; Yuyang Huang; Linlin Liu; Mingshou Lv; Bingyu Sun; Min Qu; Ying Sun; Xiuqing Zhu (Food Hydrocolloids, 2025)

Effect of freeze-thaw cycles on the quality of Yuba with different protein-lipid ratios on its protein-lipid network system - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Chemistry, 2025)

Global distribution pattern and conservation of the cosmopolitan cold-water coral species Desmophyllum dianthus under climate change - Wenhao Huang; Zongling Wang; Fangyuan Qu; Chang Zhao; Miaozhuang Zheng; Zhaohui Zhang; Shenghao Liu; Qinzeng Xu; Xuelei Zhang; Linlin Zhao (Journal of Environmental Management, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Algae-inspired chitosan-pullulan-based multifunctional hydrogel for enhanced wound healing - Taishan Liu; Huan Lei; Linlin Qu; Chenhui Zhu; Xiaoxuan Ma; Daidi Fan (Carbohydrate Polymers, 2025)

Umbrella effect of spotted seal conservation and achieving 30 × 30 targets in the Yellow Sea ecoregion - Hongfei Zhuang; Fangyuan Qu; Zhichuang Lu; Linlin Zhao; Zhaohui Zhang (Reviews in Fish Biology and Fisheries, 2024)

ChatEV: Predicting electric vehicle charging demand as natural language processing - Haohao Qu; Han Li; Linlin You; Rui Zhu; Jinyue Yan; Paolo Santi; Carlo Ratti; Chau Yuen (Transportation Research Part D: Transport and Environment, 2024)

Unraveling the effect of electricity price on electric vehicle charging behavior: A case study in Shenzhen, China - Haoxuan Kuang; Xinyu Zhang; Haohao Qu; Linlin You; Rui Zhu; Jun Li (Sustainable Cities and Society, 2024)

Biomass-derived carbon dots with pharmacological activity for biomedicine: Recent advances and future perspectives - Yue Liu; Linlin Zhang; Huijuan Cai; Xiaoli Qu; Junbiao Chang; Geoffrey I.N. Waterhouse; Siyu Lu (Science Bulletin, 2024)

Functional molecules surface segregation engineering in electrospinning: Design, regulation, and applications - Linlin Cao; Chen Qu; Jingchong Liu; Wenhui Li; Lihua Jiang; Boyu Jing; Chuandong Wu; Jiemin Liu (Chemical Engineering Journal, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Effect-directed analysis of androgenic compounds from sewage sludges in China - Tongtong Xiang; Chunzhen Shi; Yunhe Guo; Jie Zhang; Weicui Min; Jiazheng Sun; Jifu Liu; Xiliang Yan; Yanna Liu; Linlin Yao; Yuxiang Mao; Xiaoxi Yang; et al. (Water Research, 2024)

Influence of mixing uniformity between stabilisation materials and contaminated soil on the stabilisation efficiency of heavy metals - Yunlong Zhang; Lixia Sun; Bo Wu; Meng Zhang; Shuhai Guo; Linlin Li; Shuqi Li; Longlong Qu (Journal of Environmental Chemical Engineering, 2024)

Effects of glutenin/gliadin ratio and calcium ion on the structure and gelatinity of wheat gluten protein under heat induction - Min Qu; Peixiu Jiang; Ying Zhu; Xiuqing Zhu; Linlin Liu; Yuyang Huang (Food Bioscience, 2024)

Ginsenoside Rk1 induces autophagy-dependent apoptosis in hepatocellular carcinoma by AMPK/mTOR signaling pathway - Huanyan Wu; Linlin Qu; Xue Bai; Chenhui Zhu; Yuan Liu; Zhiguang Duan; Hongyan Liu; Rongzhan Fu; Daidi Fan (Food and Chemical Toxicology, 2024)

Clinical Application of Polygenic Risk Score in IgA Nephropathy - Linlin Xu; Ting Gan; Pei Chen; Yang Liu; Shu Qu; Sufang Shi; Lijun Liu; Xujie Zhou; Jicheng Lv; Hong Zhang (Phenomics, 2024)

Dynamic behaviors of cavitation bubbles near biomimetic surfaces: A numerical study - Hongbo Shi; Hang Zhang; Linlin Geng; Sen Qu; Xikun Wang; Petr A. Nikrityuk (Ocean Engineering, 2024)

The effect of internal structure on dynamic response of road-metro tunnels under train vibration loads: An experimental study - Wenqi Guo; Wenbo Yang; Zhihao Qian; Linlin Yang; Chuan He; Shuai Qu (Tunnelling and Underground Space Technology, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Development of SSR markers on the basis of the Panax notoginseng transcriptome for agronomic and biochemical trait association analyses - Linlin Su; Yingpeng Zhang; Ye Yang; Yuan Qu; Xiuming Cui; Feng Ge; Diqiu Liu (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

High Fischer ratio peptide of hemp seed: Preparation and anti-fatigue evaluation in vivo and in vitro - Zhu Ying; Huang Yuyang; Li Meiying; Sun Bingyu; Liu Linlin; Lv Mingshou; Qu Min; Guan Huanan; Zhu Xiuqing (Food Research International, 2023)

Ginsenoside Rh4 remodels the periphery microenvironment by targeting the brain-gut axis to alleviate depression-like behaviors - Jingjing Shao; Xiaoxuan Ma; Linlin Qu; Pei Ma; Rong Huang; Daidi Fan (Food Chemistry, 2023)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Development of genome-wide SNPs for population genetics of Collichthys lucidus - Linlin Zhao; Meijie Jiang; Fangyuan Qu; Dan Yi; Shouqiang Wang; Zhaohui Zhang (Conservation Genetics Resources, 2018)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Structural controls on joint development in the southeastern margin of the Ordos basin - Linlin Wang; Bo Jiang; Jilin Wang; Zhenghui Qu; Run Chen (Arabian Journal of Geosciences, 2016)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Structural control on pore-fracture characteristics of coals from Xinjing coal mine, northeastern Qinshui basin, China - Jiegang Liu; Bo Jiang; Ming Li; Zhenghui Qu; Linlin Wang; Lei Li (Arabian Journal of Geosciences, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Alternative splicing and immune response of Crassostrea gigas tumor necrosis factor receptor-associated factor 3 - Baoyu Huang; Linlin Zhang; Yishuai Du; Li Li; Tao Qu; Jie Meng; Guofan Zhang (Molecular Biology Reports, 2014)

Bioaugmentation of Bromoamine Acid Degradation with Sphingomonas xenophaga QYY and DNA Fingerprint Analysis of Augmented Systems - Yuanyuan Qu; Jiti Zhou; Jing Wang; Zhiyong Song; Linlin Xing; Xiang Fu (Biodegradation, 2006)